Early Mixing in Bilingual Children: A Psycholinguistics View - Dwi Ide Rahayu (Tell : Teaching of English Language and Literature Journal, 2018)
Most studies on Bilinguals First Language Acquisition (BFLA) are concerned with giving explanation for language mixing in young bilinguals. It is commonly stated that language mixing in children has to be interpreted as evidence for confusions in the bilingual’s language acquisition, in the sense that the two languages are not acquired separately but start out as a single system. In other words, it is in contrast to adults’ code-switching. In this article, early mixing in bilingual children is explored based on psycholinguistics view. This article will first discuss the language acquisition, then the theories and assumptions on bilingualism in early childhood, and last the early mixing in bilingual children. According to the review of related literature, it can be inferred that from psycholinguistics view, language mixing cannot indicate the bilingual children’s lack of ability to differentiate the two language system. Spontaneous translation employed by the bilingual children shows that bilingual awareness and language differentiation is possible at an early stage. Bilingual infants can do language mixing as an evidence of their meta-linguistic awareness and language differentiation. As language mixing may be a good indicator of bilingual fluency, we can say that children who become bilingual in their early childhood will reach their fluency in the two languages by doing language mixing according to the two languages they have acquired.